Prophets, policy-makers and advocates: The World Council of Churches and institutional environmental ethics, 1991-2006 - Mcfee, Daniel (Studies in religion, 2009)
The World Council of Churches (WCC) addresses environmental issues in three modes in its institutional work as a religious non-governmental organization: in the prophetic mode, in the public policy expert mode and in the mode of an advocate. If one is to understand the WCC’s commitment to environmental issues, this three-tiered hermeneutic is necessary so that its complex institutional aims are represented accurately. Moreover, this hermeneutic also aids in sketching the WCC’s larger ethical commitments as a Christian body and as a consultative religious non-governmental organization within the United Nations. This paper affords a more complete vision than many scholars have offered in terms of how religious NGOs approach extraordinarily complex ethical issues in the world today.Le Conseil oecuménique des Églises (COE) s’adresse aux questions environnementales en trois modes dans son travail institutionnel comme organisation non-gouvernementale religieuse : le mode prophétique, le mode d’expert en affaires publiques, et le mode d’un avocat. Si on veut comprendre l’engagement du COE aux problèmes environnementaux, cet herméneutique à trois gradins est necessaire pour que ses objectifs institutionnels complexes soient representés fidèlement. D’ailleurs, cet herméneutique aide aussi à esquisser les engagements moraux plus grands du COE comme organisme chrétien et comme organisation non-gouvernementale religieuse au sein de l’Organisation des nations unies. La communication présente permet une vision plus complète que celles offertes par plusieurs savants en ce qui concerne la manière dans laquelle les ONG religieuses abordent des questions morales extrêmement complexes du monde d’aujourd’hui.